Novel creatine biosensors based on all solid-state contact ammonium-selective membrane electrodes - Altikatoglu, Melda; Karakus, Emine; Erci, Vildan; Pekyardimci, Sule; Isildak, Ibrahim (TAYLOR & FRANCIS LTD, 2013)
Novel creatine bienzymatic potentiometric biosensors were prepared by immobilizing urease and creatinase on all solid-state contact PVC-containing palmitic acid and carboxylated PVC matrix membrane ammonium-selective electrodes without inner reference solution. Potentiometric characteristics of biosensors were examined in physiological model solutions at different creatine concentrations. The linear working range and long-term sensitivity of the biosensors were also determined. The creatine biosensors prepared by using the carboxylated PVC membrane electrodes showed more effective performance than those of the PVC containing palmitic acid membrane electrodes. Creatine assay in serum samples was successfully carried out by using the standard addition method.
Keywords: Creatine; all solid-state biosensors; potentiometry; carboxylated PVC; palmitic acid; POTENTIOMETRIC BIOSENSORS; FLOW-INJECTION; PVC MEMBRANE; URIC-ACID; UREA; SYSTEM; PH; Biotechnology & Applied Microbiology; Engineering; Materials Science